Faktor Pengaruh di antara Keunggulan Gereja Romawi dan Awal Mula Hari Minggu - Davied Yosua Abraham Zebedeus (Jurnal Koinonia, 2021)
The debate between the mysterious rise of Sunday observance and the church dominance in the Roman empire throughout the Ante-Nicene period appeared as an emerging discourse in regard to the Sabbath adherence. The historical background has been capable of analyzing the supposed relation between the two when the Christian beliefs gradually developed. The connection would seem to bring relevant ramifications to today’s theological understanding as far as observing the Sabbath or Sunday is concerned. The significant factors between the beginning of Sunday and the supremacy of the Roman church appeared to be intertwined and fused in the early church era. While many other events have circulated the social and religious cultures in Rome, the factors below indicate and strengthen the relationship between both church primacy and Sunday origin in history through a documentary research method. The time of the early church in this discussion is delimited around the year 100 up to 313 AD. Though the focus not only touches on one particular reason as to why Sunday replaced Sabbath, the research questions comprise of how the pre-eminence of papal supremacy took place and why the Sunday worship has seemed to alter the Sabbath observance since then.